Clinical and neuroimaging markers of neurodegeneration in first-degree relatives of patients with REM sleep behavior disorder with and without isolated rapid eye movement sleep without atonia: A case-control clinical and dopamine PET study - Chau, Steven Wai Ho; Liu, Yaping; Zhang, Jihui; Leung, Eric; Chen, Sirong; Ho, Chi Lai; Chan, Joey Wing Yan; Tsang, Chi Ching; Li, Shirley X.; Huang, Bei; Lam, Siu Ping; Mok, Vincent CT; et al. (Parkinsonism & related disorders, 2023)
The current study aimed to examine the neurodegenerative implication of isolated REM sleep without atonia (RSWA) among first-degree relatives of patients with REM sleep behaviour disorder (RBD). This cross-sectional case-control study recruited three groups of subjects: First-degree relatives of RBD patients with isolated RSWA (n = 17), first-degree relatives of RBD patients without isolated RSWA (n = 18), and normal controls who did not have any RWSA and family history of RBD (n = 15). Prodromal Parkinson's Disease likelihood ratio by the updated MDS Research Criteria and striatal dopaminergic transmission function of the subjects as assessed by triple-tracer (18F-DOPA, 11C-Raclopride, and 18F-FDG) PET/CT scan were used as proxy markers of neurodegeneration. In contrary to our hypothesis, the three groups did not differ in their pre- or post-striatal dopaminergic transmission function, and their Prodromal Parkinson's Disease likelihood ratio. However, they differed significantly in their frequency of a having first-degree relatives with Parkinson's disease or dementia of Lewy body (first-degree relativess with RSWA vs first degree relatives without RSWA vs normal controls = 58.8% vs 22.2% vs 0%, p = 0.001). FDRs of RBD patients with isolated RSWA did not have increased neurodegenerative markers compared to FDRs of RBD patients without isolated RSWA and normal control, despite an paradoxical increase in frequency of Parkinson's disease or dementia of Lewy body among their family compared to FDRs of RBD patients without isolated RSWA. Further longitudinal follow-up study will be needed to ascertain their long-term prognosis. •No difference in striatal dopaminergic function between first-degree relatives of RBD patients with or without isolated RSWA.•No difference in neurodegenerative risk markers between first-degree relatives of RBD patients with or without isolated RSWA.•Higher frequency of having Parkinson's disease or DLB among first-degree relatives of subjects with isolated RSWA.